Other Englands : utopia, capital, and empire in an age of transition - Hogan, Sarah (Professor of English) (Stanford University Press, 2018)
This book examines the rise of the early English utopia in the context of emergent capitalism, one that foreshadows the Enlightenment discourse of political economy while giving us another historical perspective on the beginnings and enduring conflicts of global capital.